Molding compositions and articles made therefrom

JP7641092B2Active Publication Date: 2025-03-06クレイトン·ポリマーズ·ネーデルラント·ベー·フェー
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020086452
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-20
Filing Date
2020-05-18
Publication Date
2025-03-06
Estimated Expiration
2040-05-18

Smart Images

  • Figure 0007641092000001
    Figure 0007641092000001
  • Figure 0007641092000002
    Figure 0007641092000002
Patent Text Reader

Abstract

To provide injection molded articles having improved scratch resistance and reduced gloss change after heat aging and UV aging.SOLUTION: An article is formed from a molding composition having a melt flow index of 50-350 g / 10 min (230°C, 2.16 kg), the composition consisting essentially of: a) 15-80 wt.% of a hydrogenated styrenic block copolymer having a melt index of at least 12 grams / 10 min at 230°C and 2.16 kgf; b) 10-60 wt.% of a polypropylene having a melt flow index greater than 300 g / 10 min, measured under 230°C / 2.16 kg according to ISO 1133-1; and c) 5-25 wt.% of a thermoplastic vulcanizate having a Shore A hardness of 60-90 (15 sec, 23°C). The article has a gloss increase of less than 100% after 10 days of aging at 120°C, relative to an initial gloss, as determined by PSA D47 1850.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This disclosure relates to molding compositions, methods for preparing them, and articles made therefrom. [Background technology]

[0002] Soft feel materials have found applications in many industries, for example in automotive interior parts such as interior trim, interior coverings, door panels, instrument panels and consoles. The electronics industry also utilizes soft feel materials for protective covers and grips for handheld devices. Other applications include, but are not limited to, tool handles, toothbrushes, overmolding and injection molding applications.

[0003] Much effort has been put into developing polymer compositions that exhibit desirable properties, lower cost, or both. For some applications, it is desirable to improve one or more of the tactile characteristics, low gloss surface appearance, or durability characteristics of the polymer article. For vehicles, it is desirable to use materials that have a sensory perception of softness and long-lasting resistance to frequent contact and scratching, since passengers come into contact with the interior of the vehicle. One method of imparting a soft-touch feel is single- or multi-step injection molding of a thermoplastic or plastic composition to form the article. In a multi-step process, a second layer of functional material is applied on top of the molded article by overmolding, painting, or other techniques. Summary of the Invention [Problem to be solved by the invention]

[0004] There remains a need for improved polymer compositions that have one or more desirable properties including low gloss, mar resistance, scratch resistance, low temperature toughness, dimensional stability, or a combination thereof, and that exhibit a relatively soft-feeling hand feel. [Means for solving the problem]

[0005] Summary of the Invention In one aspect, the present disclosure relates to an injection molded article comprising a) a polymerizable compound having the general formula: SES, (SE 1 ) n , (S.E. 1 ) n S, (S.E. 1 ) n A hydrogenated styrenic block copolymer having a molecular weight of 5,000 to 7,000, an S block having a molecular weight of 5,000 to 7,000, an E block having a molecular weight of 30,000 to 70,000, and a mixture thereof, wherein n has a value of 2 to 6, and X is a coupling agent residue, and the S block is a polystyrene block having a molecular weight of 5,000 to 7,000, an E block is a polydiene block having a molecular weight of 30,000 to 70,000, and the .... 1 a) 15-80% by weight of a hydrogenated styrenic block copolymer, the block being a polydiene block selected from the group consisting of polybutadiene, polyisoprene and mixtures thereof, having a molecular weight of 15,000-35,000; b) 10-60% by weight of polypropylene; and c) 5-25% by weight of a thermoplastic vulcanizate; the hydrogenated styrenic block copolymer has a melt index of at least 12 g / 10 min at 230° C. and 2.16 kg weight according to ASTM D1238; the polypropylene has a melt flow index of greater than 300 g / 10 min when measured according to ISO 1133-1 condition 230° C. / 2.16 kg; the thermoplastic vulcanizate has a Shore A hardness of 60-90 (15 sec, 23° C.) when measured according to ISO 868; and the molding composition is It has a melt flow index of 50 to 350 g / 10 min (230°C, 2.16 kg) as measured by D1238-04; and the injection molded article after 10 days aging at 120°C has a % gloss increase of less than 100 relative to the initial gloss as determined by PSA D47 1850.

[0006] In one aspect, the disclosure relates to a method of preparing an injection molded article by the steps of: (a) forming a molding composition as described above; and (b) forming an injection molded article from the molding composition by injection molding, overmolding, rotomolding, thermoforming, casting, extrusion, profile extrusion, or blow molding. The injection molded article after 10 days of aging at 120° C. has a gloss value, as determined by PSA D47 1850, that is at least 100% greater than the gloss value of the article before aging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The following terms are used herein and have the following meanings.

[0008] "Molecular weight" refers to the styrene equivalent molecular weight of a polymer block or block copolymer in g / mol. Molecular weight can be measured by gel permeation chromatography (GPC) using polystyrene calibration standards, for example, according to ASTM 5296-19. The chromatograph is calibrated using commercially available polystyrene molecular weight standards. The molecular weight of the polymer measured using GPC so calibrated is the styrene equivalent molecular weight. The styrene equivalent molecular weight can be converted to true molecular weight if the styrene content of the polymer and the vinyl content of the diene segments are known. The detector can be a combination of ultraviolet and refractive index detector. The molecular weights expressed herein are measured at the peak of the GPC trace and converted to true molecular weight, commonly referred to as "peak molecular weight" and indicated as Mp. Unless converted to true molecular weight as described above, this molecular weight refers to the styrene equivalent peak molecular weight.

[0009] "True molecular weight" of a polymer block or copolymer refers to the styrene equivalent molecular weight determined using GPC and polystyrene calibration standards according to ASTM 5296-11.

[0010] "Vinyl content" refers to the content of conjugated dienes polymerized by 1,2-addition in the case of butadiene or by 3,4-addition in the case of isoprene.

[0011] The "polystyrene content" or PSC of a block copolymer refers to the weight percent of polystyrene in the block copolymer, calculated by dividing the sum of the molecular weights of all polystyrene blocks by the total molecular weight of the block copolymer. PSC can be determined using proton nuclear magnetic resonance (NMR).

[0012] The "melt flow index" of the components in the molding composition is measured according to ISO 1133-1 at a temperature of 230° C. and a load of 2.16 kg. The melt flow index of the molding composition can be measured according to ASTM D1238-04 at a temperature of 230° C. and a load of 2.16 kg.

[0013] "Shore A hardness" is a measurement of the indentation resistance of an elastomeric or soft plastic material based on the depth of penetration of a conical indenter, and may be measured according to ISO-868.

[0014] "Scratch resistance" is a measure of resistance to scratching and can be determined in accordance with PSA D45-5523.

[0015] "Density" can be measured using test method ISO 1103.

[0016] "Gloss" can be measured according to PSA D47 1850.

[0017] The present disclosure relates to an article made by injection molding, in which the molded layer is one-component, two-component or overmolded and has improved scratch, abrasion and reduced gloss change characteristics after thermal and UV aging, the layer consisting essentially of a styrenic block copolymer, a high flow polypropylene and a thermoplastic vulcanizate.

[0018] Styrenic Block Copolymer (SBC) Component: The injection molded layer comprises one or more styrenic block copolymers, each characterized by having a high melt flow rate of at least 12 g / 10 min (230° C. / 2.16 kg).

[0019] In an embodiment, HSBC has the general formula: SES, (SE 1 ) n , (S.E. 1 ) n S, (S.E. 1 ) n X or mixtures thereof, where n has a value of 2 to 6 and X is a coupling agent residue. The SBC comprises less than 15% by weight of a compound of the general formula SE or SE 1 Prior to hydrogenation, the S blocks are polystyrene blocks. Each of the S blocks has a molecular weight of 5,000 to 7,000. Prior to hydrogenation, the E blocks are polydiene blocks selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a molecular weight of 30,000 to 70,000. Prior to hydrogenation, the E blocks are polydiene blocks selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a molecular weight of 30,000 to 70,000. 1 The blocks are polydiene blocks selected from the group consisting of polybutadiene, polyisoprene and mixtures thereof and having a molecular weight of 15,000 to 35,000.

[0020] In an embodiment, the styrene content of the block copolymer is 13-25 wt%. The vinyl content of the polydiene block prior to hydrogenation is 70-85 mol%. After hydrogenation, about 0-10% of the styrene double bonds are hydrogenated and at least 80% of the conjugated diene double bonds are hydrogenated. In an embodiment, the HSBC has a melt index according to ASTM D1238 at 230° C. and 2.16 kg weight of at least 12 grams / 10 minutes, or at least 20 grams / 10 minutes, or at least 75 grams / 10 minutes.

[0021] In yet another embodiment, the SBC (a) has a number average molecular weight of 44,000 to 80,000 and is represented by the general formula (AB): 4 (b) a 4-branch block copolymer (IV) having a number average molecular weight of 33,000 to 60,000 and having the general formula (AB) 3 (c) a tri-branched block copolymer (III) having a number average molecular weight of 22,000 to 40,000 and represented by the general formula (AB) 2 and (d) 2-10 weight percent of a linear diblock copolymer (I) having a number average molecular weight of 11,000-20,000 and represented by the general formula AB. In these formulas, A represents a polymer block of a monoalkenyl arene having a number average molecular weight in the range of 4,000-7,000 g / mol. B represents a polymer block of a conjugated diene having a number average molecular weight in the range of 7,000-13,000 g / mol. X represents the residue of an alkoxysilane coupling agent. SBC has a vinyl content of 30-50 mol%.

[0022] In yet a third embodiment, the SBC is a polymeric block having an ultra-high melt flow rate (melt index of 80 to 600 g / 10 min at 190° C. and 2.16 kg weight) of S block and E or E 1 blocks, and having the general formula: SES, (SE 1 ) n In these formulas, n has a value of 2-6, X is a coupling agent residue, and the molecular weight of the S block is 4,400-5,600 g / mol. The polystyrene content in the block copolymer is 25-40 wt.%. Up to 50 wt.% of the diblock units in the block copolymer have the general formula SE or SE 1Prior to hydrogenation, the S block is a polystyrene block; the E block is a polydiene block selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a molecular weight of 18,000 to 26,000 g / mol; 1 The blocks are polydiene blocks selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, and have a molecular weight of 9,000 to 13,000 g / mol. The total vinyl content of the polydiene blocks is 60 to 85%. After hydrogenation, there is a reduction of 0 to 10 percent of the styrene double bonds in the block copolymer and at least 80 percent of the conjugated diene double bonds in the block copolymer.

[0023] The SBC component is present in an amount of 15-80% by weight, or 20-80% by weight, or 30-80% by weight, or 40-80% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, based on the total weight of the molding composition. In an embodiment, the SBC component is a mixture of at least two different SBCs in a weight ratio in the range of 20:40 to 40:20, or 25:35 to 35:25, or 30:30 to 30:30, or 35:25 to 25:35.

[0024] Polypropylene Component: In embodiments, the polypropylene may be (i) a homopolymer of propylene, (ii) a homopolymer of propylene with ethylene and C 4 ~C 10 (iii) a random copolymer of propylene with an olefin selected from α-olefins and ethylene and C 4 ~C 10 The high flow polypropylene is selected from the group consisting of random terpolymers of two α-olefins selected from the group consisting of α-olefins. 4 ~C 10 As α-olefins, linear and branched C 4 ~C 10α-olefins such as 1-butene, 1-pentene, 4-methyl-pentene-1, 3-methyl-1-butene, 1-hexene, 3,4-dimethyl-1-butene, 1-heptene, 3-methyl-1-hexene, and 1-octene.

[0025] In an embodiment, the propylene polymer is a heterophasic propylene copolymer ("HECO") The copolymer comprises a polypropylene matrix having three different polypropylene fractions, the three polypropylene fractions differing in melt flow rate, the HECO having a melt flow rate (230°C) of 20.0 g / 10 min or greater, measured according to ISO 1133.

[0026] In an embodiment, the propylene polymer has a melt flow of greater than 30 dg / min, or at least 50 dg / min, or at least 60 dg / min, or at least 70 dg / min, or at least 80 dg / min, as measured by ASTM D1238-82 (230°C / 5 kg). In an embodiment, the polypropylene has a melt flow of greater than 500 g / 10 min (230°C, 2.16 kg), or greater than 800 g / 10 min, or greater than 900 g / 10 min, or greater than 1000 g / 10 min, as measured according to ISO 1131-1. In an embodiment, the polypropylene has ultra-high melt flow properties of at least 1500 g / 10 min, or at least 1800 g / 10 min, or at least 1850 g / 10 min. In one embodiment, the propylene component is a homopolymer of propylene.

[0027] Propylene is present in the molding composition in an amount of 10-60% by weight, or 10-55% by weight, or 15-50% by weight, or 15-40% by weight, or 20-40% by weight, or 20-30% by weight, based on the total weight of the molding composition.

[0028] Thermoplastic vulcanizate (TPV) component: TPV refers to a thermoplastic elastomer with a cured elastomeric phase dispersed in a thermoplastic material. TPVs are sometimes also referred to as "elastoplastic" or "heterophasic" compositions. TPVs include at least a thermoplastic material and at least one cured (i.e., crosslinked) elastomeric material. The thermoplastic material forms the matrix or continuous phase, and the cured elastomer forms a discontinuous phase with domains of cured elastomer dispersed in the thermoplastic matrix. In embodiments, the domains of cured elastomer are uniformly dispersed in the continuous phase of the thermoplastic material.

[0029] In an embodiment, the TPV is based on a blend of ethylene-propylene-diene elastomeric polymers or ethylene-α-olefin-diene elastomeric polymers with semi-crystalline or crystalline polymers, and is made by dynamically curing the rubber and resin blend. One example is a dynamically vulcanized alloy of mostly fully cured ethylene propylene diene methylene (EPDM) rubber particles encapsulated in a polypropylene matrix. In another example, the TPV comprises a microgel dispersion of cured elastomers, such as EPDM rubber, butyl rubber, chlorinated butyl rubber, polybutadiene or polyisoprene, in an uncured matrix of a thermoplastic polymer such as polypropylene. The TPV can be prepared by polymerization of one or more, usually two or more α-monoolefins, preferably with a polyene, generally a diene, as disclosed in the prior art.

[0030] In an embodiment, the TPV is made of an ethylene-α-olefin-diene monomer elastomeric polymer containing vinylnorbornene as the diene monomer, a crystalline or semi-crystalline thermoplastic resin, and a curing agent. The TPV has an ethylene content of 40-90 mol % and 0.2-4 mol % vinylnorbornene, with the remainder typically being an α-olefin, with propylene being preferred. The thermoplastic component is selected from polypropylene, polyethylene, polybutylene or copolymers thereof, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyamide (PA), and combinations thereof. The curing agent is typically a peroxide. The TPV has a Mooney viscosity (ML) of at least 10 at 125°C.

[0031] In an embodiment, the TPV comprises a blend of an olefinic rubber having a high Mooney viscosity and a thermoplastic olefinic resin, the rubber being cured with a phenolic curative, the rubber being in the form of particles having a number average size of less than 50 microns, the rubber having a Mooney viscosity of at least 100 MU as measured on uncured raw rubber.

[0032] In an embodiment, the TPV comprises a propylene-based polymer as the continuous phase of the TPV and a crosslinked olefin block copolymer (OBC) dispersed as a discontinuous phase in the propylene-based polymer. The OBC refers to a multi-block or segmented copolymer having linearly connected segments (or blocks) including a propylene α-olefin copolymer, a scorch retardant, and a crosslinker. The propylene α-olefin can be either a propylene / ethylene copolymer or a random propylene / ethylene copolymer.

[0033] In an embodiment, after the TPV is compounded, the molten TPV compound is extruded through a 200 mesh or finer screen to further enhance surface smoothness.

[0034] In an embodiment, the TPV has a high melt flow rate of at least 10 g / 10 min (ISO 1133 230° C. / 2.16 kg), or at least 15 g / 10 min, or at least 20 g / 10 min. In an embodiment, the TPV has a Shore A hardness (15 sec, 23° C.) of 60-90 or 64-80, as measured by ISO 868 test method; 3 or 0.900~0.970g / cm 3 The TPV may be either an extrusion grade TPV or a molding grade TPV having a density of

[0035] The TPV is present in an amount of 5-25 wt%, or 7-20 wt%, or 10-20 wt%, or at least 7 wt%, or at least 10 wt%, based on the total weight of the molding composition.

[0036] Additives: In embodiments, the composition further comprises one or more additives selected from nucleating agents, clarifying agents, release agents, plasticizers, antioxidants, stabilizers (e.g., heat stabilizers, visible light stabilizers, UV stabilizers), colorants, flame retardants, lubricants (e.g., calcium stearate), synergists, mold release agents, flow enhancers, antistatic agents, glass fillers, fillers different from glass fillers (e.g., talc), scratch resistant additives / surface modifiers (e.g., silicones, low density polyethylene which may be long chain branched low density polyethylene), or a combination comprising at least one of the foregoing.

[0037] In an embodiment, the plasticizer is a mineral oil. Examples of suitable oils include hydrocarbon-based oils having an average molecular weight in the range of about 100 to about 1000 g / mol (calculated from the kinematic viscosity according to ASTM D2502).

[0038] Examples of surface modifiers include ultra-high molecular weight polydialkylsiloxanes, such as polydimethylsiloxane, ultra-high molecular weight polydialkylsiloxanes in combination with silica, polyolefin siloxanes, and combinations thereof.

[0039] The additives may be present in an amount of from 1 to 15% by weight, or from 3 to 13% by weight, or less than 10% by weight, based on the total weight of the molding composition.

[0040] Properties of the molding composition: The molding composition is characterized by having a melt flow index of at least 50 g / 10 min (230° C., 2.16 kg as measured by ASTM D1238-04) or at least 60 g / 10 min or at least 70 g / 10 min or from 50 to 250 g / 10 min or from 50 to 350 g / 10 min or at least 90 g / 10 min or at least 100 g / 10 min.

[0041] Methods of processing the composition / molding article: The molding composition can be processed by methods known in the art, where the components are combined and blended / extruded into pellets by melt mixing, followed by forming the article by known techniques, such as injection molding, overmolding, rotational molding, thermoforming, casting, extrusion, profile extrusion, and blow molding.

[0042] In one embodiment, the molding composition is injected onto a polyolefin layer or substrate to form an article, and to adhere the molding composition to the polyolefin layer or substrate by fusion, the polyolefin layer or substrate can be heated to a first temperature of about 180° C. to 240° C. and held at this temperature during fusion and solidification of the blend.

[0043] In an embodiment, the molding composition, either alone or overmolded as a layer onto a polyolefin substrate, forms a layer having a thickness of at least 0.5 mm, or from 0.5 to 2.0 mm, or from 0.8 to 1.4 mm, or from 0.9 to 1.2 mm, or less than 3.0 mm.

[0044] Properties of molded articles: Articles made from the molding compositions in embodiments have initial gloss measurements as determined at 60° by PSA D47 1850 of less than 5 or less than 3 or less than 2 or less than 1.5. After 10 days aging at 120° C., the gloss is less than 10 or less than 7 or less than 5 or less than 4. After 10 days aging at 120° C., the articles have a % gloss increase of less than 100 or less than 70 or less than 50 or less than 30 or less than 10.

[0045] In embodiments, articles made from the molding compositions have very good scratch resistance when measured according to PSA D54 5523 with a load of 3 Newtons (N).

[0046] In embodiments, the molded articles have excellent color fastness or wilting at moderate (85° C.) or elevated temperatures (100° C.) after heat aging and exposure to light, as measured according to D47 1431, with the color change measured before and after exposure to light.

[0047] Applications: The molding compositions can be used for automotive applications, such as interior trim, interior covering, door panels, instrument panels and consoles, with good thermal stability, scratch resistance and improved gloss values ​​after aging. The molding compositions are useful in injection molding, overmolding and extrusion applications. EXAMPLES

[0048] The examples are given for illustrative purposes only.

[0049] Examples 1 to 9 The ingredients in Table 1 were compounded, pelletized by twin screw extruder, then injection molded into 2mm thick grained imitation leather and evaluated. The test samples were aged in a hot air oven at 120°C for 240 hours (10 days), at which point the gloss was measured by a glossmeter with a 60 degree angle. The scratch resistance test was performed by an Erichsen 318s pencil. The scratch resistance rating can be determined and indicated as negative sign (-) = negative result and positive sign (+) = positive result. The more positive signs (+, ++ or +++), the better the scratch resistance. The results are as shown in the table.

[0050] The main components used in the examples are as follows:

[0051] HFPP1 is a high flow polypropylene with a melt flow rate of 800 g / 10 min (230° C. / 2.16 kg).

[0052] HFPP2 is a high flow polypropylene with a melt flow rate of 1200 g / 10 min (230° C. / 2.16 kg).

[0053] HFPP3 has a narrow molecular weight distribution of 0.90 g / cm 3 and a melt flow (230°C / 2.16kg) of 1200g / 10min.

[0054] TPV is 0.970g / cm 3 a Shore A hardness of 69 at 15 seconds, 23°C, 2.00 mm (ISO 688); a phenolic cured blend of polypropylene and ethylene propylene diene (EPDM) copolymer having a tensile stress in the 100% cross flow direction (23°C) of 2.60 MPa and a tensile strength at break in the cross flow direction (23°C) of 7.00 MPa, and an elongation at break in the cross flow direction of 450%, all according to ASTM D412.

[0055] HSBC53 is a styrene-ethylene-butylene-styrene (SEBS) block copolymer with a melt flow rate of 20-28 g / 10 min (230° C. / 2.16 kg), 30 wt. % PSC, less than 10 wt. % diblock concentration, and a Shore A hardness of 73.

[0056] HSBC48 is a low molecular weight SEBS polymer with an ultra-high melt flow rate of 220 g / 10 min at 230° C. and 2.16 kg, a tensile strength of 11 MPa and an elongation at break of 750%.

[0057] [Table 1]

[0058] Examples 10 to 15 The example is repeated, except using two different SBCs as shown in Table 2. Samples were injection moulded into 1 mm thick JLR grain plaques and evaluated as in the previous example, with the results shown in the table below.

[0059] [Table 2]

Claims

1. 1. An article formed from a composition, the composition comprising: a) General formula: SE-S, (SE 1 ) n , (S-E 1 ) n S, (S-E 1 ) n X or mixtures thereof, where n has a value from 2 to 6 and X is the residue of a coupling agent; Before hydrogenation, the S block is a polystyrene block having a styrene equivalent peak molecular weight of 5,000 to 7,000 as measured in accordance with ASTM 5296-19; the E block is a polydiene block selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a styrene equivalent peak molecular weight of 30,000 to 70,000 as measured in accordance with ASTM 5296-19; E 1 the blocks are polydiene blocks selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a styrene equivalent peak molecular weight of 15,000 to 35,000 as measured in accordance with ASTM 5296-19; 15-80% by weight of hydrogenated styrenic block copolymer; b) 10 to 60% by weight of polypropylene; and c) Thermoplastic vulcanizate 5-25% by weight Including, each of the hydrogenated styrenic block copolymers has a melt index of at least 12 g / 10 min at 230° C. and 2.16 kg weight according to ASTM D1238; The polypropylene has a melt flow index, measured in accordance with ISO 1133-1, condition 230° C. / 2.16 kg, greater than 300 g / 10 min; The thermoplastic vulcanizate has a Shore A hardness, measured according to ISO 868, of 60 to 90 (15 seconds, 23°C); the composition has a melt flow index, as measured by ASTM D1238-04, of 50 to 350 g / 10 min (230° C., 2.16 kg); The article after aging for 10 days at 120° C. has an increase in gloss of less than 100% relative to the initial gloss before aging, as determined by PSA D47 1850; Goods.

2. 10. The article of claim 1, wherein the thermoplastic vulcanizate is a dynamically vulcanized alloy comprising fully cured ethylene propylene diene methylene rubber particles encapsulated in a polypropylene matrix.

3. The thermoplastic vulcanizate has a modulus of 0.880 to 0.980 g / cm3 as measured by ISO 1183. 3 The article of claim 1 having a density of

4. The article of claim 1 , wherein the composition forms a layer having a thickness of at least 0.5 mm.

5. Polypropylene is (i) a homopolymer of propylene, (ii) a homopolymer of propylene with ethylene and C 4 ~C 10 (iii) random copolymers of propylene with ethylene and C 4 ~C 10 The article of claim 1, wherein the polymer is selected from a random terpolymer with two α-olefins selected from the group of α-olefins.

6. 10. The article of claim 1, further comprising 1 to 15 weight percent of one or more additives selected from the group consisting of nucleating agents, clarifying agents, release agents, plasticizers, antioxidants, heat stabilizers, visible light stabilizers, UV stabilizers, colorants, flame retardants, lubricants, synergists, mold release agents, flow enhancers, antistatic agents, fillers, scratch resistant additives, and surface modifiers.

7. 10. The article of claim 1 formed by any of injection molding, overmolding, rotational molding, thermoforming, casting, extrusion, profile extrusion, and blow molding.

8. 10. The article of claim 1 having a gloss level of 10 or less at 60° C. as measured by PSA D47 1850.

9. 10. The article of claim 1, having a gloss value of 15 or less as measured by PSA D47 1850 after 10 days aging at 120°C.

10. 1. A method of preparing an article, comprising: (a) forming a composition, said composition comprising: a) General formula: SE-S, (SE 1 ) n , (S-E 1 ) n S, (S-E 1 ) n X or mixtures thereof, where n has a value from 2 to 6 and X is the residue of a coupling agent; Before hydrogenation, the S block is a polystyrene block having a styrene equivalent peak molecular weight of 5,000 to 7,000 as measured in accordance with ASTM 5296-19; the E block is a polydiene block selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a styrene equivalent peak molecular weight of 30,000 to 70,000 as measured in accordance with ASTM 5296-19; E 1 the blocks are polydiene blocks selected from the group consisting of polybutadiene, polyisoprene, and mixtures thereof, having a styrene equivalent peak molecular weight of 15,000 to 35,000 as measured in accordance with ASTM 5296-19; 15-80% by weight of hydrogenated styrenic block copolymer; b) 10 to 60% by weight of polypropylene; and c) Thermoplastic vulcanizate 5-25% by weight The steps include: and (b) forming the article from the composition by injection molding, overmolding, rotational molding, thermoforming, casting, extrusion, profile extrusion, or blow molding. is formed by each of the hydrogenated styrenic block copolymers has a melt index of at least 12 g / 10 min at 230° C. and 2.16 kg weight according to ASTM D1238; The polypropylene has a melt flow index, measured in accordance with ISO 1133-1, condition 230° C. / 2.16 kg, greater than 300 g / 10 min; The thermoplastic vulcanizate has a Shore A hardness, measured according to ISO 868, of 60 to 90 (15 seconds, 23°C); the composition has a melt flow index, as measured by ASTM D1238-04, of 50 to 350 g / 10 min (230° C., 2.16 kg); The article after aging for 10 days at 120° C. has an increase in gloss of less than 100% relative to the initial gloss before aging, as determined by PSA D47 1850; method.

11. The method of claim 10 , wherein step (b) comprises forming a layer having a thickness of at least 0.5 mm.

Citation Information

Patent Citations

  • Low temperature injection moldable composition

    JP1982137342A

  • Thermoplastic olefin elastomer composition for air bag cover material

    JP1996113677A

  • Thermoplastic elastomer composition for boot and boot using the same

    JP2002317096A

  • Thermoplastic elastomer composition for slush molding, powder and skin formed therefrom

    JP2006016620A

  • Cross-linked composition, method for producing cross-linked composition, and molding

    WO2013039220A1